2021
DOI: 10.1002/pits.22585
|View full text |Cite
|
Sign up to set email alerts
|

Examining teachers' judgment of students' 21st century skills and academic and behavioral outcomes

Abstract: In this study we examined the relationship of students' 21st century skills with their academic and behavioral outcomes. We investigated K‐12 teachers' (n = 150) judgment of students' (n = 3,108) use of 21st century skills (i.e., persistence, curiosity, affect, and cognition behaviors) via a Likert‐type rating scale. We compared teachers' ratings with students' academic and behavioral outcomes in a southeastern school district. We used Hierarchical Linear Modeling with length of teacher acquaintance with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…These ICCs indicated a non-ignorable portion of the total variance in ratings was due to the between-teacher variability. Likewise, another study reported the ICC of students’ mathematics and science scores of 0.25 and 0.19, respectively (Woods-Groves et al, 2021), indicating again a substantial amount of the between-teacher variance in predicting students’ mathematics and science outcomes. In sum, the proportion of variability in teacher ratings that lies between teachers has been shown to range from 10% to 33% and depends on the domain assessed.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…These ICCs indicated a non-ignorable portion of the total variance in ratings was due to the between-teacher variability. Likewise, another study reported the ICC of students’ mathematics and science scores of 0.25 and 0.19, respectively (Woods-Groves et al, 2021), indicating again a substantial amount of the between-teacher variance in predicting students’ mathematics and science outcomes. In sum, the proportion of variability in teacher ratings that lies between teachers has been shown to range from 10% to 33% and depends on the domain assessed.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, in the science domain, teacher ratings appeared to have a positive relationship with students' science performance, but again there is variability between teachers in these ratings (Herman & Choi, 2008). Specifically, teachers appeared to be better equipped to rate students in their science outcomes relative to the length of acquaintance-teachers who had known students for a longer period of time were able to rate their students' science ability more accurately compared to those who had not (Woods-Groves et al, 2021). In addition, when teachers received sufficient training on how to use the teacher rating scales in the science domain, teachers were found to be more capable of rating their students' science abilities (Renzulli et al, 2010).…”
Section: Variability In Teacher Ratings Of Student Abilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students are expected by their teachers to engage in motivational behaviors such as curiosity and perseverance, demonstrate social-emotional competence, and take part in cognition behaviors. With these abilities (Woods-Groves et al, 2021). Education in the 21st century is required to meet competency standards in accordance with current global trends.…”
Section: Introductionmentioning
confidence: 99%